Design thinking na elaboração de um produto educacional: roteiro de aprendizagem – estruturação e orientações - Farias, Marcella Sarah Filgueiras de (2019)
Directed study is a technique that uses learning scripts to guide students in autonomously conducting their learning. Although the literature deals with directed study, we identified a lack of guidelines for the elaboration and application of learning scripts. This observation led us to the objective of this research, which elements can be used to compose specific orientations that help teachers to elaborate learning scripts for their students ?. In view of the problem in question, we use Design Thinking as a methodological path to develop an educational product that aims to indicate a structure of learning script and guidelines for its application by teachers in their teaching context. This product was materialized on a website, a learning script template, downloadable guidance material, and supplemental support videos. Due to the very nature of the adopted path (iterative, interactive and incremental), two DT application cycles were performed to reach the results of the research and development of the mentioned products. The results of this research contribute to the increase of the literature on directed study as it produced a theoretical and practical material to assist our target audience, teachers of elementary, high school and (Youth and Adult Education) in the elaboration and application. of learning scripts. In addition, materializing the educational product across different media improves teacher access and autonomous learning.